PENGALAMAN ORANG TUA DALAM MERAWAT ANAK THALASSEMIA MAYOR - Leni Rozani; Ferasinta Ferasinta; Muhammad Bagus Andrianto (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2022)
Thalassemia is a hereditary disease caused by the failure of the formation of one of the four amino acid chains that make up hemoglobin, so that hemoglobin is not formed completely. The purpose of this study was to explore in depth the experiences of parents in caring for children with thalassemia at Dr. Hospital. M. Yunus Bengkulu City, where researchers collected data and information through observation and interviews with informants. This research is qualitative research with a phenomenological research method. Informants in this study involved 3 parents who were obtained by purposive sampling technique. Data were obtained through in-depth interviews. The results of this study found the themes of parents' experiences in caring for thalassemia major children, namely aspects of knowledge, aspects of handling, physical and mental aspects, and aspects of hope. The responses of parents during their time as respondents in the study were shown by experience in treating children with thalassemia, knowledge problems, handling problems, physical and mental problems, and hope problems.